THU0508 Safety and Efficacy of Tocilizumab in Patients with Systemic Juvenile Idiopathic Arthritis: 5-Year Data from Tender, A Phase 3 Clinical Trial. (9th June 2015) - De Benedetti, F.; Ruperto, N.; Brunner, H.; Keane, C.; Wells, C.; Wang, J.; Calvo, I.; Cuttica, R.; Ravelli, A.; Schneider, R.; Eleftheriou, D.; Wouters, C.; et al.
Abstract : Background: Two-year results from the 3-part, 5-year, phase 3 TENDER study demonstrated that tocilizumab (TCZ), an anti–interleukin-6 receptor antibody, was effective in the treatment of patients with severe, persistent systemic juvenile idiopathic arthritis (sJIA). 1 Objectives: To report the long-term safety and efficacy of TCZ in patients with sJIA treated for up to 5 years in the TENDER trial. Methods: In part 1, patients (2-17 years) with active sJIA for ≥6 months were randomly assigned 2:1 to receive TCZ (body weight [BW] ≥30 kg, TCZ 8 mg/kg; BW <30 kg, TCZ 12 mg/kg) or placebo every 2 weeks (q2w) for 12 weeks. Patients received open-label TCZ q2w based on BW in part 2 (weeks 12-104) and part 3 (weeks 104-260). In part 3, an alternative dosing regimen in which TCZ and concomitant medications were tapered and discontinued in patients with clinically inactive disease (CID) was optional. Efficacy was assessed in those who entered part 3 (ITT3 population) and up to the point of entry into the alternative dosing schedule; safety was assessed in all patients who entered part 1 (safety population). The primary end point in part 3 was long-term safety. Results: Of the 112 patients enrolled in part 1, 89 entered part 3 and were included in the ITT3 population; 66 patients (59%) completed the full 260-week study. Patients in the ITT3 population had a mean (SD) age of 9.5 (4.4) years, and 53% were male. The high proportion of patients achieving JIA ACR 30/50/70/90 responses on entry into part 3 was maintained through week 260 (Table 1 ). Among the 30 patients who did not enter the alternative dosing regimen and completed the study, 8 (26.7%) met the criteria for CID at week 260. During the study, an additional 39 patients reached and maintained CID for at least 3 months and entered the alternative dosing regimen. Of patients remaining in the study at week 260, 31 received oral glucocorticoids (GCs) and 34 received methotrexate (MTX) at baseline. By the end of the study, 17/31 and 6/34 patients stopped oral GCs and MTX, respectively. The 5-year safety profile for patients on q2w dosing was similar to the 2-year safety profile, with no new safety findings observed (Table 2 ). Rates/100 patient-years (PY) of adverse events (AEs) and of serious AEs (SAEs) did not increase between year 2 and year 5 (Table 2 ). Most SAEs were unrelated to study treatment, and infections accounted for nearly half of all SAEs. Four deaths occurred over the 5 years at a rate of 1.1/100 PY; 1 death (sepsis) was possibly related to study treatment. Conclusions: These results demonstrate the continued maintenance of efficacy and no change in the safety profile over 5 years of TCZ treatment in patients with sJIA. References: De Benedetti F et al. Ann Rheum Dis. 2012;71(suppl 3):425. Disclosure of Interest: F. De Benedetti Grant/research support from: Roche, Novartis, Pfizer, Novimmune, Sobi, Consultant for: Roche, Novartis, N. Ruperto Grant/research support from: Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Consultant for: Roche, Speakers bureau: Abbott, AbbVie, Amgen, Astellas, Bristol Myers-Squibb, Boehringer, Celgene, CrescendoBio, EMDSerono, Italfarmaco, Janssen, Medimmune, Novartis, Novonordisk, Pfizer, Sanofi, Reumatic.com, Servier, Sinergie, Takeda, H. Brunner: None declared, C. Keane Employee of: Roche, C. Wells Employee of: Roche, J. Wang Employee of: Roche, I. Calvo: None declared, R. Cuttica: None declared, A. Ravelli Grant/research support from: Pfizer, Consultant for: Novartis, Roche, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Pfizer, R. Schneider Consultant for: Roche, Novartis, D. Eleftheriou: None declared, C. Wouters: None declared, R. Xavier Consultant for: Roche, Janssen, Pfizer, AstraZeneca, AbbVie, L. Zemel: None declared, E. Baildam Grant/research support from: Roche, Chugai, Speakers bureau: Roche, R. Burgos-Vargas: None declared, P. Dolezalova Grant/research support from: Novartis, Consultant for: Roche, Novartis, Pfizer, S. Garay: None declared, R. Joos: None declared, A. Grom Consultant for: Novartis, Genentech, N. Wulffraat Grant/research support from: European Union (EAHC), Z. Zuber: None declared, F. Zulian: None declared, A. Martini Grant/research support from: Roche, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Novartis, Pfizer, Sanofi Aventis, Schwarz Biosciences GmbH, Consultant for: Roche, Speakers bureau: Roche, Abbott, AbbVie, Amgen, Astellas, Bristol-Myers Squibb, Boehringer, Celgene, CrescendoBio, EMDSerono, Italfarmaco, Janssen, Medimmune, Novartis, Novo Nordisk, Pfizer, Sanofi, Servier, Takeda, D. Lovell Grant/research support from: NIH, Consultant for: AstraZeneca, Bristol-Myers Squibb, AbbVie, Pfizer, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Biogen, Takeda, Genentech, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Janssen, Speakers bureau: Genentech, Roche, Novartis